Chronic behavior disturbance and neurocognitive deficits in neuro-Behcet's disease: a case study. Issue 3 (3rd May 2016) - Fisher, Caroline A.; Sewell, Katherine; Baker, Amy
ABSTRACT: Behcet's disease is a vasculitis and multisystem inflammatory syndrome. Neurological abnormalities occur in a subset of patients. This report presents a case of neuro-Behcet's disease characterized by an initial onset of behavior changes prior to diagnosis, which evolved into a chronic behavioral syndrome. Neuroimaging investigations revealed progressive periventricular white matter and brainstem atrophy and lesions in the basal ganglia and deep white matter tracts, while neuropsychological investigations revealed reductions in information processing, executive functioning, and memory. The case indicates that behavior changes may be the first symptoms to emerge in Behcet's, before other defining features of the disease.